PALEOTECTONIC AND PALEOGEOGRAPHIC CONDITIONS FOR THE ACCUMULATION OF THE LOWER RIPHEAN AI FORMATION IN THE BASHKIR UPLIFT (SOUTHERN URALS): THE TERRANECHRONE® DETRITAL ZIRCON STUDY - T. V. Romanyuk; N. B. Kuznetsov; E. A. Belousova; V. M. Gorozhanin; E. N. Gorozhanina (Геодинамика и тектонофизика, 2018)
The TerraneChrone® (LA-ICP-MS) technique has been applied to carry out an integrated study of detrital zircons in sandstones sampled from the basal horizons of the stratotypical Riphean sequence in the Southern Urals, specifically the Navysh and Chudin suites of the Ai Formation of the Burzyan Group in the Bashkir Uplift. The concentrations of trace elements in the detrital zircons suggest that the role of oceanic or marginal-marine complexes among the primary sources of zircons was insignificant, and show a better agreement with the intra-continental rather than passive-margin origin of the Riphean basin, whose basal levels are composed by the Ai Formation. The U/Pb ages of zircons from samples K13-206 and M08-16-1 are generally similar: the Paleoproterozoic zircons predominate (the dominant peaks are actually coincident, 2063 and 2055 Ma), and only a few grains of the Archean age are present. Despite the similar U/Pb ages of the detrital zircons, these two samples considerably differ in their Hf isotopic features and the concentrations of trace elements, which means that the zircons in the studied sandstones are of different geodynamic origin. The characteristics of these zircons can be explained by a model showing the Ai Formation in the Navysh graben that is a rift structure and a predecessor of the Kama-Belaya aulacogene in the inner Volga-Ural region of the Paleoproterozoic supercontinent Columbia. At the initial stage of rifting, the granitoid complexes with a lower total silicic acidity, which composed the graben walls, had been eroded; as a result of erosion, coarse clastic rocks accumulated within the Navysh graben and formed the Navysh suite. A specific “carbonatitic” complex containing zircons (about 2.0, 2.5, 2.85 and 3.6 Ga) and the Palaeoarchean crustal material in the substrate of their parent rocks was also eroded. In the final stage of rifting, already at the initial stages of the development of the Kama-Belaya aulacogen (Chudin suite), the erosion products from the paleo-aquifers occupying vast areas began to be transported into the rift. The primary sources of clastics for the Chudin suite were both granitoids of the lower and normal silicic acidity. Besides, a specific “carbonatitic” complex containing juvenile zircons (about 2.05 Ga) was eroded. However, by that time, significant areas of the Archaean basement of the Volga-Ural region might have become hidden underneath a proto-cover and thus not eroded, so the Archean detritus in the Chudin suite is poorly represented in comparison with the Navysh suite, considering both the amounts and ages of detrital zircons. As of today, the Precambrian carbonatite rocks within both the Taratash complex (composing the basement of the Navysh graben) and the southeastern segment of the East-European Platform have not yet been described. The source of the “carbonatite” zircons remains unknown and can be discovered as more and more data on the basement rocks is accumulated.